Gaya Komunikasi Media Podcaster Dalam Konten Podcast Pwk Di Channel You Tube Has Creative - Taufik Bawazir; Dilmai Putra; Martha Heriniazwi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The development of information and communication technology has given rise to new media that have changed the way humans interact, one of which is podcasts. Podcasts, as on-demand audio media, are now increasingly popular, including in Indonesia. One of the most popular podcasts is Podcast Warung Kopi (PWK), hosted by Praz Teguh on the HAS Creative YouTube channel. Praz Teguh is known for his relaxed, open, and expressive communication style, which creates a fluid, warm, and meaningful conversation atmosphere. This study aims to understand Praz Teguh's communication style and the types of questions he uses in the Warung Kopi Podcast (PWK). The research method used is descriptive qualitative with non-participant observation and documentation techniques on PWK episodes with Indro Warkop. The analysis was conducted using Robert W. Norton's Communicator Style Measure concept, which classifies communication styles based on verbal and nonverbal characteristics. The results show that Praz Teguh uses a combination of relaxed, open, and expressive styles. He often uses humor, spontaneity, and everyday language that makes the conversation feel close to the audience, while also slipping in reflective and humanistic values. This communication style has proven to be able to build emotional closeness with listeners and increase audience engagement. This research is expected to contribute theoretically to the development of communication science, particularly the study of podcaster communication styles, and to serve as a practical reference for content creators in building meaningful interactions with audiences in the digital media era.